2023
DOI: 10.1128/spectrum.02125-22
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacterial Dysbiosis in Irritable Bowel Syndrome: a Case-Control Study and a Cross-Cohort Analysis Using Publicly Available Data Sets

Abstract: Research on the gut bacteria in irritable bowel syndrome (IBS) shows discordant results due to inconsistent study designs or small sample sizes. To overcome these issues, we analyzed microbiota of 567 IBS patients and 487 healthy people from 10 shared data sets using a unified method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…87 Interestingly, changes in structure and composition of gut microflora occur irrespective of insulin resistance in people with PCOS, 88 contributing to the manifestations of hyperandrogenism, insulin resistance, chronic inflammation, and abnormal levels of brain-gut peptides. [89][90][91] As dysbiosis is associated with irritable bowel syndrome (IBS), 92 and IBS is reported to impact the quality of life in 21 to 27% of those diagnosed with PCOS, 93 focusing on interventions to treat dysbiosis through prebiotics, probiotics, and synbiotics is an important part of PCOS nutritional care. Probiotics are thought to stabilize the hormonal imbalance through the gut-brain axis, leading to a reduction in the LH/FSH ratio in PCOS populations.…”
Section: Lifestyle Intervention: Important With or Without Medical Th...mentioning
confidence: 99%
“…87 Interestingly, changes in structure and composition of gut microflora occur irrespective of insulin resistance in people with PCOS, 88 contributing to the manifestations of hyperandrogenism, insulin resistance, chronic inflammation, and abnormal levels of brain-gut peptides. [89][90][91] As dysbiosis is associated with irritable bowel syndrome (IBS), 92 and IBS is reported to impact the quality of life in 21 to 27% of those diagnosed with PCOS, 93 focusing on interventions to treat dysbiosis through prebiotics, probiotics, and synbiotics is an important part of PCOS nutritional care. Probiotics are thought to stabilize the hormonal imbalance through the gut-brain axis, leading to a reduction in the LH/FSH ratio in PCOS populations.…”
Section: Lifestyle Intervention: Important With or Without Medical Th...mentioning
confidence: 99%
“…However, a more recent review of 16 studies focusing on longitudinal omics studies only, showed significant heterogeneity across gut microbial characteristics in IBS cohorts across studies, concluding that defining uniform gut microbial characteristics of an IBS-related gut microbiota is challenging (Ng et al, 2023). However, while clearer characterisation of IBS-related gut microbial characteristics is needed, overall, gut microbial dysbiosis is prevalent in this cohort (Wang et al, 2020; Kim et al, 2023; Ng et al, 2023). In IBD patients, a recent meta-analysis of 13 studies showed faecal bacterial alpha diversity was lower compared to healthy controls, and this was more pronounced in CD compared to UC (Abdel-Rahman and Morgan, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…While the pathogenesis of FGIDs and IBD is complex, gut microbial dysbiosis appears to be intertwined with such gastrointestinal diseases and disorders (Xavier and Podolsky, 2007; Holtmann et al, 2016). In comparison to healthy individuals, FGID and IBD cohorts have been shown to have different gut microbial characteristics (Duan et al, 2019; Pittayanon et al, 2020; Wang et al, 2020; Clooney et al, 2021; Abdel-Rahman and Morgan, 2022; Kim et al, 2023). A 2019 systematic review of 16 studies showed IBS patients had lower faecal bacterial alpha diversity, compared to healthy controls (Duan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in this abundance will change the metabolites of the flora and threaten the health. 3 Studies have shown that the imbalance of intestinal flora is closely related to the occurrence and development of various diseases, such as irritable bowel syndrome, 4 acute anterior uveitis, 5 rheumatoid arthritis, 6 diabetes, 7 hypertension, 8 autism, 9 and colorectal cancer. 10 This article reviews the research on the correlation between intestinal flora and diseases in recent years, in order to provide new references and strategies for clinical treatment.…”
Section: Introductionmentioning
confidence: 99%